Effect of work rest ratio on cycling performance following sprint interval training. A randomized control trial - Lloyd Jones, C. M.; Morris, G. M.; Jakeman, R. J. (The Journal of Strength and Conditioning Research, 2019)
Sprint interval training (SIT) has been shown to improve performance measures in a range of individuals, and it is understood that different responses can be elicited from different training protocols. However, consideration of changes in work to rest ratios could offer important insight into optimizing training programs. The purpose of this study was to investigate the effect of 3 different work to rest ratios on exercise performance. Thirty-six male and female subjects were randomly allocated to 1 of 3 training groups or a nontraining control group. Training consisted of 10 × 6 second "all-out" sprints on a cycle ergometer, with a 1:8, 1:10, or 1:12 work-to-rest ratio. Performance data, including peak power output, performance decrement, and 10-km time trial performance data were collected before and after 2 weeks of SIT. There were significant (p = 0.05) improvements in all parameters for the training groups, but no changes were observed in the control condition. Peak power increased by 57.2, 50.7, and 53.7 W in the 1:8, 1:10 and 1:12 groups, respectively, with no significant differences in response between conditions. Time trial performance improved significantly in all 3 training conditions (29.4, 8.7, and 25.1 seconds in the 1:8, 1:10, and 1:12 groups), while worsening in the control group. All training conditions resulted in significant improvements in performance, but there were no significant differences in improvement for any of the groups. Any of the 3 stated that work to rest ratios would be appropriate for use with athletes and allow some level of personal preference for those interested in using the protocol.